Updated measurements of exclusive J/[psi] and [psi](2S) production cross-sections in pp collisions √s = 7TeV - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Journal of physics. G, Nuclear and particle physics, 2014)
The differential cross-section as a function of rapidity has been measured for the exclusive production of J/ψ and ψ(2S) mesons in proton-proton collisions at TeV, using data collected by the LHCb experiment, corresponding to an integrated luminosity of 930 pb−1. The cross-sections times branching fractions to two muons having pseudorapidities between 2.0 and 4.5 are measured to be where the first uncertainty is statistical and the second is systematic. The measurements agree with next-to-leading order QCD predictions as well as with models that include saturation effects.